Hyperlipidemia in Childhood Idiopathic Nephrotic Syndrome during Initial Remission and Relapse (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):402-406 The abstract of this article is available on the PubMed website